Heart transplantation in the UK during the first wave of the SARS‐CoV‐2 pandemic. Issue 5 (9th March 2021) - Hardman, Gillian; Sutcliffe, Ruth; Hogg, Rachel; Mumford, Lisa; Grocott, Laura; Jerrett, Lorraine; Mead‐Regan, Sarah‐Jane; Nuttall, Jane; Dunn, Stephanie; Seeley, Philip; Quigley, Richard; Dalzell, Johnathan R.; et al.
Abstract: Background: We aim to evaluate practice and understand the impact of the first wave of the SARS‐CoV‐2 pandemic on heart transplantation in the UK. Methods: A retrospective review of the UK Transplant Registry (UKTR) and a national survey of UK heart transplant centers have been performed. The early pandemic period is defined here as 1 March to 31 May 2020. Results: There was geographic variation in the prevalence of COVID‐19 across the UK. All centers reported adaptations to maintain the safety of their staff, candidate, and recipient populations. The number of donors fell by 31% during the early pandemic period. Heart utilization increased to 35%, compared to 26% during the same period of 2019. The number of heart transplants was well maintained, across all centers, with 38 performed, compared to 41 during the same period of 2019, with no change in 30‐day survival. Twenty‐seven heart transplant recipients with confirmed COVID‐19 infection were reported during the study period. Conclusion: All UK heart transplant centers have successfully adapted their programs to overcome the challenges of staff redeployment and ICU and hospital resource limitation, associated with the pandemic, whilst continuing heart transplant activity. On‐going evaluation of practice changes, with sharing of lessons learned, is required as the pandemic continues.